2015
DOI: 10.1093/mutage/geu088
|View full text |Cite
|
Sign up to set email alerts
|

XRCC1 and ERCC1 polymorphisms are related to susceptibility and survival of colorectal cancer in the Chinese population

Abstract: Excision repair cross complementing group 1 (ERCC1) and X-ray repair cross-complementing groups 1 (XRCC1) are DNA repair enzymes. Polymorphisms in DNA repair genes may be important factors affecting cancer susceptibility, prognosis and therapy outcome. The purpose of this study was to investigate the correlation of ERCC1 and XRCC1 polymorphisms with colorectal cancer (CRC) risk, and explore the effect of polymorphisms on event-free, overall survival and oxaliplatin-based therapy in CRC patients. Genotyping was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
0
30
1
Order By: Relevance
“…Moreover, Dai et al [17] showed that the XRCC1 194Arg/Trp gene polymorphism is associated with increased risk for CRC, reduced chemotherapy response, and reduced survival. Another study conducted by Nissar et al [18] among a Kashmiri population found a significant impact of the Trp/Trp and Arg/Trp genotypes on the development of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Dai et al [17] showed that the XRCC1 194Arg/Trp gene polymorphism is associated with increased risk for CRC, reduced chemotherapy response, and reduced survival. Another study conducted by Nissar et al [18] among a Kashmiri population found a significant impact of the Trp/Trp and Arg/Trp genotypes on the development of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…A number of single nucleotide polymorphisms (SNPs) in DNA repair genes have been known to affect cancer susceptibility, prognosis, and therapeutic outcomes [8]. Indeed, SNPs in drug-targeted genes [9], metabolizing enzymes [10], and DNA-repairing enzymes [11] have been linked to inter-individual differences in the efficacy and toxicity of numerous drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, SNPs in drug-targeted genes [9], metabolizing enzymes [10], and DNA-repairing enzymes [11] have been linked to inter-individual differences in the efficacy and toxicity of numerous drugs. Excision repair cross-complementing group 1 (ERCC1) and 2 (ERCC2) and X-ray repair cross-complementing group 1 (XRCC1) are DNA repair enzymes which play important roles in nucleotide excision repair [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant transformation of prostate cells is always associated with genetic alterations such as deletions, inversion and point mutations . The association between genetic factors such as several single nucleotide polymorphisms (SNPs) with various cancers such as PCa, leukemia, colorectal cancer, breast cancer, and so on, has been reported . Several lines of investigations have shown the relationship between SNPs of the genes involved in DNA repair and cancer susceptibility.…”
Section: Introductionmentioning
confidence: 99%